Vancomycin Resistance in Enterococcus faecium Strains Isolated at a University Hospital - Armindo José Perozo Mena; Maribel Josefina Castellano González; Messaria María Ginestre Pérez; Gresleida Coromoto Rincón Villalobos (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2011)
Genus Enterococcus species are gram positive cocci, usually inhabitants of human and animal intestinal tracts, but can also be isolated from their environmental sources. They are able to survive a wide range of adverse environmental stress conditions, allowing them to colonize a wide range of niches, including hospital environments. Nosocomial pathogenicity of enterococci has emerged in recent years, as well as their increased resistance to glycopeptide antibiotics. This study attempts to determine the resistance to vancomycin of Enterococcus faecium strains isolated in a university hospital during the January-December period of 2009, as well as to characterize the genetic determinant responsible for its resistance. Methods to determine susceptibility to glycopeptides described by CLSI were used; additionally, the genetic elements responsible for resistance were identified using the polymerase chain reaction. Of the E. faecium strains studied, 48.81% were resistant to vancomycin, and PCR showed presence of the vanA gene that confers high levels of resistance to glycopeptides. Due to the large number of isolates resistant to vancomycin, the presence of a nosocomial outbreak produced by this microorganism was suspected; this epidemic strain possessing a vanA gene is possibly scattered in different services of the institution; therefore, epidemiological studies should be performed to determine the role this microorganism plays in the production of nosocomial infections in the institution under study.